2022
DOI: 10.1111/cpr.13273
|View full text |Cite
|
Sign up to set email alerts
|

DNASE1L3 inhibits proliferation, invasion and metastasis of hepatocellular carcinoma by interacting with β‐catenin to promote its ubiquitin degradation pathway

Abstract: As a member of the deoxyribonuclease 1 family, DNASE1L3 plays a significant role both inside and outside the cell. However, the role of DNASE1L3 in hepatocellular carcinoma (HCC) and its molecular basis remains to be further investigated. In this study, we report that DNASE1L3 is downregulated in clinical HCC samples and evaluate the relationship between its expression and HCC clinical features. In vivo and in vitro experiments showed that DNASE1L3 negatively regulates the proliferation, invasion and metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…DNase1L3 inhibits proliferation, invasion, and metastasis of HCC. ( 22 ) This study also showed a strong association between DNase1L3 and the clinicopathology of HCC, which is a factor with good prognosis. This study explained the mechanism by which DNase1L3 inhibits tumor progression from the perspective of degrading ecDNA.…”
Section: Discussionsupporting
confidence: 62%
“…DNase1L3 inhibits proliferation, invasion, and metastasis of HCC. ( 22 ) This study also showed a strong association between DNase1L3 and the clinicopathology of HCC, which is a factor with good prognosis. This study explained the mechanism by which DNase1L3 inhibits tumor progression from the perspective of degrading ecDNA.…”
Section: Discussionsupporting
confidence: 62%
“…Cell migration and stem-like properties contribute to the aggressiveness of tumors and poor patient prognosis ( 43 ). Many proteins involved in HCC cell migration are regulated by ubiquitination, such as β-catenin ( 44 ), snail ( 45 , 46 ), and ZEB1 ( 47 ). The EMT marker, Vimentin, may also influence tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with a high DNASE1L3 expression in HCC was better than those with a low expression, as shown by Univariate Cox expression analysis (P<0.001) and Kaplan-Meier survival estimate (P<0.001). DNASE1L3 inhibits HCC by inducing apoptosis and reprogramming glucose metabolism and interacting with β-catenin to promote its ubiquitin degradation pathway ( 26 , 28 ). And DNASE1L3 is a prognostic biomarker associated in cancer ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNASE1L3 and DNASE1 can degrade DNA in the serum (19). DNASE1L3 is involved in chromatin degradation in apoptotic or necrotic cells (20)(21)(22)(23)(24)(25)(26)(27)(28). The decrease in DNASE1L3 activity is related to several autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%